Patient‐reported outcomes of a phase II neoadjuvant apalutamide (ARN‐509) and radical prostatectomy in treatment of intermediate‐ to high‐risk prostate cancer (NEAR) trial. (24th August 2022) - Yang, Xinyan; Allen, John Carson; Aslim, Edwin Jonathan; Tay, Kae Jack; Yuen, Shyi Peng John; Kanesvaran, Ravindran; Chua, Melvin Lee Kiang; Chong, Tsung Wen; Ho, Sun Sien Henry; Lee, Lui Shiong
Abstract : Objective: The NEAR trial is a single‐arm phase II trial investigating the efficacy of neoadjuvant apalutamide and radical prostatectomy in the treatment of D'Amico intermediate‐ to high‐risk prostate cancer. This publication focuses on health‐related quality of life (HRQoL) during 12 weeks of neoadjuvant apalutamide treatment. Methods: From 2017 to 2019, 30 suitable patients received neoadjuvant apalutamide 240 mg once daily for 12 weeks followed by radical prostatectomy (ClinicalTrials.gov Identifier: NCT03124433). Patient‐reported quality of life outcomes was analyzed using European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core Module (EORTC QLQ‐C30), EORTC Quality of Life Questionnaire Prostate Module (QLQ‐PR25), and Sexual Health Inventory for Men questionnaire (SHIM) at weeks 0, 4, 12, and 20 of the study. Results: Thirty patients completed 12 weeks of apalutamide therapy and data analyzed for 29 with complete datasets. Neoadjuvant apalutamide therapy was associated with no clinically significant negative impact on patients' global health and QoL scores. Deteriorations in mean scores of functional and symptom scales of QLQ‐C30 questionnaire were statistically significant ( p = 0.011 and p = 0.008, respectively) but were not clinically meaningful. Patients were also affected by fatigue ( p = 0.012), cognitive function ( p = 0.038), reduced role functioning ( p = 0.025), and lower SHIM scores ( p < 0.001). Median daily step count reduced from 8228/day to 6001/day per day ( p = 0.063), while BMI and body weight reduction were observed (statistically but not clinically significant). Conclusion: During 12 weeks of neoadjuvant apalutamide in organ‐confined prostate cancer, the overall patient‐reported HRQoL outcomes were maintained, but fatigue and sexual dysfunction were observed in those patients.